A case study on the application of the Role Method in a therapeutic theatre production at National Taiwan University of Arts. Issue 1 (1st April 2017) - Chang, Hsiao-Hua
This article presents an account of Dr Robert Landy's influence on the evolution of drama therapy in Taiwan and at the National Taiwan University of Arts. It includes case examples of two therapeutic theatre projects, which led to important insights into the use of the Role Method to develop and organize a therapeutic performance. The inclusion of a therapeutic theatre project in the training of drama therapists is now a part of our standard practice.